Heutagogy, Sebuah Alternatif Pendekatan Pembelajaran di Sekolah Dasar pada Era Revolusi Industri 4.0 - Gusti Ayu Putu Sukma Trisna; Dinn Wahyudin; Rusman Rusman; Cepi Riyana (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aimed to explore more deeply about heutagogy as a learning approach for students in elementary schools in the era of the industrial revolution 4.0 with all the dynamics of the conditions that occurred. The research method used bibliographic research by prioritizing the integrity and accuracy of sources, relationships, meaning relations, and conformity with the research focus. The data collection technique of this research was by studying the documentation of articles related to heutagogy and analyzed descriptively and qualitatively. The results of this study indicated that: (1) Heutagogy was an alternative learning that can be developed by teachers in elementary schools because this approach provided more optimal space and learning expectations for students, by making themselves the control of learning, (2) This approach heutagogy made the atmosphere and learning outcomes more interesting and motivates students to bring out all their abilities in the principles of humanity in the corridor of democratic education, and (3) The application of the heutagogy approach in elementary schools was a very wise alternative because students, facilitated by teachers, can choose and determine something they wanted to learn, without neglecting the general principles of formal learning.